Effectiveness Of Cooperative Learning Teams Games Tournament In Improving Numeracy Ability Towards Students' AKM Achievements In Junior High School - Asmahani Maulidita; Lukman Harun; Aurora Nur Aini (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
The results of the 2022 PISA assessment indicate that the numeracy skills of students in Indonesia remain in the low category, with a score of 366. This represents a decline from the 2018 PISA results, where Indonesia achieved a score of 379 in numeracy. The focus of educators is to enhance students' numeracy skills. This study aims to test the Team Games Tournament (TGT) theory and its application in mathematics learning. The primary objective of this research is to assess the effectiveness of implementing the cooperative TGT approach in improving students' numeracy skills, as measured by their achievement in the Assessment Competency Minimum (AKM) scores. The research employs a quasi-experimental design with a one-group pretest-posttest model. The study population consists of 30 participants, selected from a class of eighth-grade junior high school students using a simple random sampling technique. The research data includes pretest and posttest scores for numeracy, based on the Assessment Competency Minimum (AKM), for the participants. The data is analyzed descriptively with the assistance of SPSS version 23.0 software. Data analysis involved both descriptive and inferential statistical methods. The analysis began with a normality test, followed by a homogeneity test, and concluded with a paired sample t-test to assess the mean difference between the pretest and posttest scores. The results indicated a significant increase in the average score, from 42.33 on the pretest to 59.17 on the posttest. The implementation of the cooperative Team Games Tournament (TGT) approach proved to be effective in enhancing students' numeracy skills, as evidenced by the improvement in their numeracy AKM scores.